2022
DOI: 10.3390/biom12060797
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Linolenic Acid (GLA) Protects against Ionizing Radiation-Induced Damage: An In Vitro and In Vivo Study

Abstract: Radiation is pro-inflammatory in nature in view of its ability to induce the generation of reactive oxygen species (ROS), cytokines, chemokines, and growth factors with associated inflammatory cells. Cells are efficient in repairing radiation-induced DNA damage; however, exactly how this happens is not clear. In the present study, GLA reduced DNA damage (as evidenced by micronuclei formation) and enhanced metabolic viability, which led to an increase in the number of surviving RAW 264.7 cells in vitro by reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…GLA, DGLA, and PGE1 have potent cytoprotective and genoprotective actions against radiation, benzo(a)pyrene, 4α-phorbol, and diphenylhydantoin both in vitro and in vivo. [7][8][9][10][11][12][13] Similar cytoprotective action has also been reported with LXA4, resolvins and protectins. [14][15][16][17][18] Hence, it is suggested that these bioactive lipids prevent doxorubicin-induced cardiotoxicity by enhancing the formation of LXA4.…”
Section: Efas and Their Metabolites Are Cytoprotective And Genoprotec...supporting
confidence: 58%
“…GLA, DGLA, and PGE1 have potent cytoprotective and genoprotective actions against radiation, benzo(a)pyrene, 4α-phorbol, and diphenylhydantoin both in vitro and in vivo. [7][8][9][10][11][12][13] Similar cytoprotective action has also been reported with LXA4, resolvins and protectins. [14][15][16][17][18] Hence, it is suggested that these bioactive lipids prevent doxorubicin-induced cardiotoxicity by enhancing the formation of LXA4.…”
Section: Efas and Their Metabolites Are Cytoprotective And Genoprotec...supporting
confidence: 58%
“…According to previous reports, irradiation‐induced salivary gland damage is attributed to elevated levels of oxygen free radicals induced by irradiation. Increased oxygen free radicals could cause abnormal inflammatory responses 42 . TNF‐α, IL‐1β and IL‐6 are very important proinflammatory cytokines with a range of biological activities 43 (Figure 3H).…”
Section: Resultsmentioning
confidence: 99%
“…Increased oxygen free radicals could cause abnormal inflammatory responses. 42 TNF‐α, IL‐1β and IL‐6 are very important proinflammatory cytokines with a range of biological activities 43 (Figure 3H ). We detected the expression of TNF‐α, IL‐1β and IL‐6 via western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…This pathway resulted in a decrease in the abundance of gamma-linolenic acid (GLA) in the liver, ileum, colon, and kidney of colitis mice. GLA is an omega-6, 18 carbon PUFA, that is consumed in the diet (62). GLA is rapidly enzymatically converted into dihomo- gamma-linolenic acid (DGLA) and due to continuous conversion, it is naturally found at low levels with a corresponding increase in DGLA (63).…”
Section: Discussionmentioning
confidence: 99%